KEMAMPUAN PEMECAHAN MASALAH DAN DISPOSISI MATEMATIS SISWA MENGGUNAKAN PENDEKATAN PROBLEM-BASED LEARNING (PBL) - Zaozah, Eris Siti; Maulana, M.; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
This research purpose to prove Problem-Based Learning (PBL) approach better than conventional approach in improving problemz solving abilityz and mathematical disposition ofz students, and how is relation between problemz solving abilityz and mathematical disposition. This research method is quasi experimental, with the nonequivalent controlz group design. The populationz is the fourth graders ofz elementary school in Cimalaka sub-district the school is in the superior group, with a sampel fourth grade students of SDN Margamukti as the experimental class and the fourth grade students of SDN Cimalaka III as the control class. The instrumentss used in  this research are test and nontest instruments. The result of research with significance level α = 0,05 indicates that learning with Problem-Based Learning (PBL) approach is significantly better than conventional learning in improving problem  solving ability and   mathematical disposition of student. Theres is a positive relationship between problem solving abilities and mathematical disposition of students.